Muslim welfare organizations in Germany – Between participation, professionalization, and empowerment - Tekin, Sinem (Ревија за социјална политика/Journal of Social Policy, 2023)
Since the growth of the Muslim population in Germany, the demands for a Muslim welfare organization are getting louder. For this reason, the German Islam Conference started some projects to develop Muslim interests in welfare organizations. The landscape of the German social welfare system is dominated by six umbrella organizations. Three of these are faith-based organizations. A Muslim organization is still missing, despite some empowerment projects. There are attempts of different Muslim communities to build social services which meet the needs of spiritual and cultural sensitiveness of Muslim people and allow them to participate in the existing system. The paper is analysing perspectives of experts on a possible concept for a Muslim welfare organization. The aim is to show a possible way of organizing and implementing a national organization. The issue is discussed in expert interviews and an additional group method of a world café. The major results can improve the ongoing efforts for a culturally sensitive welfare organization. One of the key topics is the professionalization of the existing social services in mosques and other community centers. They must meet the requirements of social work to get tax exemptions and to receive government funds. Another point is to separate religious and social services in the community centers. The heterogeneity in the Muslim population must be respected and integrated in a new form of welfare organizations, which can be different from the existing faith-based welfare organizations. Another point is to implement these tasks in borough, county, and national levels.